Using common factors to identify substitution possibilities in a factor demand system with technological changes - Håvard Hungnes (Statistics Norway, Research Department, 2016)
I apply a common factor approach to identifying substitution possibilities between input factors in a factor demand system. Technological changes can lead to shifts in the relative use of input factors within an industry. Technological changes can also be common to several industries. If such common shocks are not taken into account, the estimates of the substitution elasticity might be biased. In this paper, I investigate the importance of taking account of technological changes by allowing for different kinds of common factors, both within and between industries. The estimation results show that, if technological changes are not properly taken into account, we obtain unreliable (negative) estimates of the elasticity of substitutions. When taking such changes into account, however, the estimated elasticities of substitution are positive in all the non-government industries in mainland Norway.
Keywords: C33; E23; 330; cross-sectional averages